Analysis of potable water quality in the Belisario Quevedo sector, Cuatro Esquinas neighborhood, during the period of may to september 2023 - Caillagua, Cristian; Tenelema, Henry; Toasa, David; Tovar, Dennis (Multidisciplinar (Montevideo), 2024)
The current research project had the purpose of determining the quality of drinking water in the sector of the neighborhood Cuatro Esquinas de Belisario Quevedo. The research has a non-experimental design, and its modality was quantitative, descriptive research modality, the inquiry was of bibliographic field and descriptive type. The population consisted of 10 individuals from the neighborhood to be investigated, 2 heads of household of 5 families in the neighborhood were chosen, being the main affected. The survey technique was applied